PERENCANAAN ULANG PENJADWALAN PERAWATAN MESIN EXTR UDER MENGGUNAKAN METODE RELIABILITY CENTERED MAINTENANCE DI PT STAEDTER INDONESIA - Maulana Gustiawan; Naufal Affandi (LPPM Universitas Bina Bangsa, 2021)
PT Staedtler Indonesia is one of the best companies from Germany and is one of the leading manufacturers of stationery in the world that has an extruder machine for making pencils from plastic raw materials. To maintain the condition of the production machine is always in the best condition, the role of maintenance is very important, the damage that often occurs in the extruder machine results in the amount of time the engine downtime. With unscheduled maintenance at this time the damage occurred suddenly, causing a long repair time and resulting in many losses to the company.The analysis of this research aims to determine the application of the Realibility Centered Mintenance method can provide optimal scheduling results in the maintenance of extruder machines so that damage to the machine can be prevented and reduced so that there is no downtime on the extruder machine.The method or approach in this study uses the Realibility Centered Maintenance method by applying qualitative analysis by carrying out MTBF calculations, determining or identifying the causes and consequences of damage or failure of engine components using FMEA, analyzing critical components using Pareto diagrams and determining actions or activities in maintenance scheduling using RCM Work decision. The results showed that of the 9 components, 5 including the head body, water hose electric motor, vacuum and cutter, the maintenance scheduling used a scheduled restoration task. This conclusion indicates that the most appropriate maintenance in the maintenance of extruder machine components scheduled restoration task, which means that the maintenance uses preventive maintenance